2015
DOI: 10.1136/jnnp-2014-310068
|View full text |Cite
|
Sign up to set email alerts
|

Time to recanalisation in patients with cerebral venous thrombosis under anticoagulation therapy

Abstract: We found that recanalisation occurs over time, until month 11. Complete recanalisation may influence functional outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
46
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 15 publications
11
46
0
5
Order By: Relevance
“…We confirmed that patients with full recanalization have a better functional outcome. Similar data were published recently by Arouz et al [17]. These patients are also younger; more often female and taking contraceptive pills (if female).…”
Section: Citationsupporting
confidence: 77%
See 1 more Smart Citation
“…We confirmed that patients with full recanalization have a better functional outcome. Similar data were published recently by Arouz et al [17]. These patients are also younger; more often female and taking contraceptive pills (if female).…”
Section: Citationsupporting
confidence: 77%
“…These patients are also younger; more often female and taking contraceptive pills (if female). Recanalization occurs mainly in the first 3-4 month after thrombosis but can happen within the first year from diagnosis [17,18]. It might be important to extend anticoagulation treatment (usually with LMWH or warfarin) till 1 year in cases where only partial or none recanalization was observed [11,19].…”
Section: Citationmentioning
confidence: 99%
“…Finally, we selected 19 studies. [4][5][6][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] A MOOSE/PRISMA flowchart summarizes study selection, including the reasons for exclusion (Figure 1). Details of the studies are displayed in the Table. The 19 studies included a total of 818 patients with recanalization data after CVT ranging from 10 to 125 patients per study.…”
Section: Resultsmentioning
confidence: 99%
“…3 Importantly, studies assessing the relationship between venous recanalization and prognosis in patients with CVT have shown conflicting results. [4][5][6] One possible explanation could be the variable extent and function of collateral circulation, which was not analyzed in these cohorts. However, an independent effect of venous collateral circulation on the prognosis of patients with CVT has not been shown previously.…”
mentioning
confidence: 99%
“…Low-molecular-weight heparin was found to be superior to unfractionated heparin (37). It has been shown that recanalization starts after 3 months and increases within the first 12 months at various rates (38). It has been suggested that anticoagulation should be continued for 6 months with vitamin K antagonists after the acute phase (22,39,40).…”
Section: Treatmentmentioning
confidence: 99%